Analisis Kesesuaian Kawasanbagi Penanaman Buah-Buahan di Perlis, Malaysia: Area Suitability Analysis for Fruit Cultivation in Perlis, Malaysia - Sabri, Nur Faizah; Othman, Zainudin; Marzuki, Mazdi; Nayan, Nasir (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2013)
This article intend to study the suitability of area for selected fruit cultivation in Perlis. Temperature and relative humidity readings were collected in the field observed while informations about land use, soil series, topography and annual rainfall were obtained from related government agencies. Spatial interpolation analysis were done by using ArcGis 9.3 software based on IDW technique. This IDW technique was for assuming value and data of the whole area. Reclassification and raster calculation process were done to the involved variables to determine the suitability area for fruit cultivation. AHP technique also was applied to determine the suitability area for fruit cultivation. The highest weight value showed that the variables have relative significance and high inclination in determining the suitability of fruit cultivation. Results showed that all area in Perlis has potential and suitable for cultivation of selected fruits. This study directly benefited the agricultural sector in Perlis in planning delineating and cultivating suitable areas for growing particular crop.